'Teacher as Professional' as Metaphor: What it Highlights and What it Hides. Issue 1 (11th September 2014) - Maxwell, Bruce
<x xml:space="preserve">Abstract</x> This article is concerned with the downsides of using the language of professionalism in educational discourse. It suggests that the language of professionalization can be a powerful rhetorical device for promoting welcome and necessary changes in the field of teaching but that, in doing so, it can unintentionally misrepresent the work that teachers do. Taking as a theoretical framework Lakoff and Johnson's metaphor theory, the article argues that 'teacher as professional' should be seen as a metaphor of teaching on par with other metaphors familiar from the history of educational thought. What metaphors of teaching have in common, the article advances, is that they systematically highlight certain aspects of teaching while hiding others. The significance of this conclusion is twofold. Appreciating the limits of the 'teacher as professional' metaphor provides guidance about how to use more effectively 'professionalism' as a normative standard for promoting change in teaching and teacher education. Second, appreciating the metaphorical character of 'teacher as professional' has heuristic value in that it offers a novel explanation for the controversial trend towards conceptualising teaching in narrowly instructional terms.